Sin city? - Pieter A. Gautier; Michael Svarer; Coen N. Teulings (Institute for the Study of Labor (IZA), 2007)
Is moving to the countryside a credible commitment device for couples? We investigate whether lowering the arrival rate of potential alternative partners by moving to a less populated area lowers the dissolution risk for a sample of Danish couples. We find that of the couples who married in the city, the ones who stay in the city have significant higher divorce rates. Similarly, for the couples who married outside the city, the ones who move to the city are more likely to divorce. This correlation can be explained by both a causal and a sorting effect. We disentangle them by using the timing-of-events approach. In addition we use information on father's location as an instrument. We find that the sorting effect dominates. Moving to the countryside is therefore not a cheap way to prolong relationships.
urn:nbn:de:101:1-20080416328
Keywords: 330; Wohnstandort; Stadt; Ländlicher Raum; Binnenwanderung; Soziale Beziehungen; Ehe; Dänemark